Tomada de decisão no comércio social: o uso das recomendações online no processamento da informação de produtos com diferentes níveis de envolvimento - Radons, Daiane Lindner (2022)
The online environment provides a wealth of information for individuals purchase decision, especially social commerce, which makes accessible the opinions and positive and negative recommendations of other consumers about products and brands. However, human information processing capacity is limited and multiple information sources and communication requirements can result in cognitive overload, affecting decision-making. In this way, people often seek other consumers comments and ratings as part of their consumption decisions, which implies using these recommendations to complement and replace the information provided by product sellers. In addition, variables at the individual level, such as the involvement level with the product, influence individuals' search for information. In this sense, this study aims to verify the online product recommendations (OPRs) use as complementary and substitute information in the product information processing with different involvement levels by the individual in social commerce. A quasi-experiment was developed with two decision tasks: i) booking a hotel; and, ii) purchase a television, from the manipulation of the variables information quantity (less x more) and involvement level with the product (low x high). For data collection, eye tracker equipment and questionnaires were used. Data analysis comprised descriptive analyses, based on the metrics fixations quantity and duration of the participants, recorded by the eye tracker, besides non-parametric tests: Mann-Whitney Test and Wilcoxon Signs Rank Test. The results show that online product recommendations are the main criterion considered by the participants when choosing a hotel and TV. The Mann-Whitney test performance for the fixations recorded in the OPRs item resulted in only one significant difference, indicating that individuals highly involved with the hotel and exposed to more information tend to dedicate themselves to the systematic information processing. The dual role of recommendations was found, as substitute and complementary information. It was also found that the involvement level with the product influences information processing. Regarding the effect of the product type, no significant differences were identified in all groups, attesting that, regardless of the object of analysis, the participants followed a pattern of information analysis. The study presents theoretical and practical implications that can help researchers and managers in understanding the decision-making process in online environments.